2009
DOI: 10.1017/s0007114509991899
|View full text |Cite
|
Sign up to set email alerts
|

Fermented wheat aleurone inhibits growth and induces apoptosis in human HT29 colon adenocarcinoma cells

Abstract: Fermentation of dietary fibre by the gut microflora may enhance levels of SCFA, which are potentially chemoprotective against colon cancer. Functional food containing wheat aleurone may prevent cancer by influencing cell cycle and cell death. We investigated effects of fermented wheat aleurone on growth and apoptosis of HT29 cells. Wheat aleurone, flour and bran were digested and fermented in vitro. The resulting fermentation supernatants (fs) were analysed for their major metabolites (SCFA, bile acids and amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 37 publications
15
55
0
Order By: Relevance
“…The fermentation process led to a significant increase in SCFA with a shift of molar ratios toward butyrate as well as a reduction in the pH value in the FS of in vitro fermented nut samples. These results are in line with former studies which have shown that the fermentation of dietary fiber or fiber-rich foods results in the formation of SCFA and concurrently in lower pH values [31,32]. Similar results have also been obtained by Lux et al [22], who applied different types of nuts to an in vitro simulated digestion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The fermentation process led to a significant increase in SCFA with a shift of molar ratios toward butyrate as well as a reduction in the pH value in the FS of in vitro fermented nut samples. These results are in line with former studies which have shown that the fermentation of dietary fiber or fiber-rich foods results in the formation of SCFA and concurrently in lower pH values [31,32]. Similar results have also been obtained by Lux et al [22], who applied different types of nuts to an in vitro simulated digestion.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the SCFA-mediated lowering of pH values in the FS might lead to reduced solubility of secondary BA as well as a reduction in 7α-dehydroxylase activity, which catalyzes the conversion of primary into secondary BA [50]. The results of the present study are in line with former studies, which have also shown a reduction in secondary BA concentrations upon in vitro fermentation of different dietary fiber sources [22,24,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with former studies which revealed induction of apoptosis in LT97 cells by FS obtained from different raw nut varieties including macadamia nuts [18], or other dietary fiber sources producing butyrate as fermentation end product [29,30,38]. Again, no direct impact of different roasting conditions on apoptotic potential of fermented macadamia nuts could be observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with other studies demonstrating growth inhibition of LT97 colon adenoma [18] or HT29 colon carcinoma cells [28] by FS obtained from different raw nut varieties including macadamia. Growth inhibition of colon adenoma or cancer cells could also be shown for FS obtained from other dietary fiber rich sources such as bread [29] or wheat aleurone [30], respectively. In the present study, the roasting process had no distinct effect on the growth inhibitory potential of macadamia nuts, indicating that growth inhibition is caused by substances resulting from fermentation of macadamia nut samples such as butyrate which is unaffected by an upstream heat treatment of the nuts.…”
Section: Discussionmentioning
confidence: 90%
“…Bread samples and control samples (reagent blank as well as inulin (Synergy1 Ò ; Beneo-Orafti, Mannheim, Germany)) were subjected to an in vitro digestion after Aura, Härkönen, Fabritius, and Poutanen (1999) and Barry et al (1995) as described by Borowicki et al (2010).…”
Section: In Vitro Digestionmentioning
confidence: 99%